“Literatūros lankai”: Dialogue with Polish Literature - Adomavičienė, Laimutė (Respectus Philologicus, 2024)
The article explores the translations of Polish literary publications in the Lithuanian Exile Literature Magazine Literaturos Lankai (Literary Folios, during the period 1952–1959). Like many of its contemporaries, Literaturos Lankai expanded the scope of foreign literature in its pages through translations. The staff of the magazine continued the Lithuanian tradition by presenting Polish poets related to Lithuania: Czesław Milosz (1911–2004) and Julian Tuwim (1894–1953). New readers were introduced to the poetry of the Polish exile Jerzy Pietrkewicz (Peterkiewicz) (1916–2007) whose writings so far have been almost not translated into Lithuanian. In exile, translator Juozas Kėkštas (1915–1981) played a pivotal role in disseminating of Milosz’s highlighting his multifaceted talents as a poet, prose writer, and literary critic. Milosz offers to break out of the feelings and impressions in Chalk Circle poetry, seeking a language that reflects epic consciousness and new forms of expression. The works of Polish authors published in Literatūros Lankai reflect the ‘pulse of the time’, revealing a disturbed lyrical subject and an ongoing quest for new artistic forms. The translations of Polish literature strengthened the literary and cultural connections between Lithuania and Poland.
Keywords: Literary Folios; Polish literature in Lithuanian translations; Czesław Miłosz; Julian Tuwim; Jerzy Pietrkiewicz (Peterkiewicz)